Correlation of human sperm centrosomal proteins with fertility - Indira Hinduja; Nishitha B Baliga; Kusum Zaveri (Wolters Kluwer Medknow Publications, 2010)
Objective: The centrosome is the microtubule organizing center (MTOC) paternally inherited by the zygote during fertilization. As the centrosome is located in the midpiece of the sperm tail, we presume that oligoasthenozoospermic sperm samples should also have abnormal concentrations of centrosomal proteins. This study therefore aims to determine if there is any correlation between sperm centrosomal proteins, centrin, a and g-tubulin, in sperm samples from normozoospermic and oligoasthenozoospermic men. Materials and Methods: Proteins were extracted from the normozoospermic and oligoasthenozoospermic sperm samples and analyzed by Western Blot and ELISA for centrin, α and γ-tubulin. Results: The levels of centrin, α and γ-tubulin are markedly lower in oligoasthenozoospermic sperm samples as compared to the normozoospermic sperm samples. Conclusions: Lower centrosomal protein expression in sperm samples of oligoasthenozoospermic infertile males may be a possible cause for their reduced fertility status. Further studies on these proteins are warranted to design rational approaches for the diagnosis and treatment of male infertility.